TRACING THE POSITIVE IMPACT OF ORGANIC AGRICULTURE FOR FOOD SECURITY: A REVIEW OF RECENT LITERATURE - Loso Judijanto (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This research explores the positive impact of organic farming on food security through a review of recent literature. Organic farming, which avoids the use of synthetic chemicals, contributes to improved environmental health by improving soil fertility, reducing water pollution, and increasing biodiversity. Organic produce offers higher food safety due to the lack of pesticide residues, and often contains better nutrients such as vitamins and antioxidants. In addition to environmental and health benefits, organic farming also provides economic and social advantages for farmers, such as premium prices and the creation of new jobs. These findings underline the vital role organic farming plays in achieving sustainable and inclusive food security.